Adverse effects of methylene blue in peripheral neurons: An in vitro electrophysiology and cell culture study. (18th November 2022) - Uhelski, Megan L; Johns, Malcolm E; Horrmann, Alec; Mohamed, Sadiq; Sohail, Ayesha; Khasabova, Iryna A; Simone, Donald A; Banik, Ratan K
Methylene blue (MB) is an effective treatment for methemoglobinemia, ifosfamide-induced encephalopathy, cyanide poisoning, and refractory vasoplegia. However, clinical case reports and preclinical studies indicate potentially neurotoxic activity of MB at certain concentrations. The exact mechanisms of MB neurotoxicity are not known, and while the effects of MB on neuronal tissue from different brain regions and myenteric ganglia have been examined, its effects on primary afferent neurons from dorsal root ganglia (DRG) have not been studied. Mouse DRG were exposed to MB (0.3–10 μM) in vitro to assess neurite outgrowth. Increasing concentrations of MB (0.3–10 μM) were associated with neurotoxicity as shown by a substantial loss of cells with neurite formation, particularly at 10 μM. In parallel experiments, cultured rat DRG neurons were treated with MB (100 μM) to examine how MB affects electrical membrane properties of small-diameter sensory neurons. MB decreased peak inward and outward current densities, decreased action potential amplitude, overshoot, afterhyperpolarization, increased action potential rise time, and decreased action potential firing in response to current stimulation. MB induced dose-dependent toxicity in peripheral neurons, in vitro . These findings are consistent with studies in brain and myenteric ganglion neurons showing increased neuronal loss and altered membrane electrical properties after MB application. Further research is needed to parse out the toxicity profile for MB to minimize damage to neuronal structures and reduce side effects in clinical settings.